The Role of Judges in Criminal Case Evidence : A Comparative Study between Indonesia and Thailand - Bagas tegar prayoga Tegar Prayoga; Faisal (Jurnal Hukum Magnum Opus, 2026)
This study aims to analyze the role of judges in the criminal evidence system based on the Indonesian Criminal Procedure Code (Kitab Undang-Undang Hukum Acara Pidana/KUHAP) and the Criminal Procedure Code of Thailand, as well as to identify the fundamental differences arising from the characteristics of each country’s judicial system. This research employs a normative legal research method using statutory, conceptual, and comparative approaches through document analysis of relevant literature and regulations. The findings indicate that Indonesia adopts the negative statutory evidentiary system (negatief wettelijk bewijstheorie), as regulated in Article 183 of the KUHAP, which requires at least two valid pieces of evidence accompanied by the judge’s conviction. The role of judges is active but remains within a strict procedural framework. Meanwhile, Thailand applies a mixed adversarial–inquisitorial system with a standard of proof of beyond reasonable doubt without a minimum evidentiary requirement. The Thai Criminal Procedure Code grants judges broad authority to examine facts, question witnesses, and order the collection of additional evidence, as stipulated in Sections 228, 229, and 235. A comparison of the two systems shows that Thailand positions judges as more dominant truth-finders, whereas Indonesia emphasizes a balance between formal legality and judicial conviction. These findings provide a comprehensive understanding of the structural and philosophical implications of both systems in the enforcement of criminal justice.